Zinc for the treatment of diarrhoea: effect on diarrhoea morbidity, mortality and incidence of future episodes - Walker, Christa L Fischer (Oxford University Press, 2010)
Background Zinc supplementation for the treatment of diarrhoea has been shown to decrease the duration and severity of the diarrhoeal episode, diarrhoea hospitalization rates and, in some studies, all-cause mortality. Using multiple outcome measures, we sought to estimate the effect of zinc for the treatment of diarrhoea on diarrhoea mortality and subsequent pneumonia mortality. Methods We conducted a systematic review of efficacy and effectiveness studies. We used a standardized abstraction and grading format and performed meta-analyses for all outcomes with ≥2 data points. The estimated effect on diarrhoea mortality was determined by applying the standard Child Health Epidemiology Reference Group rules for multiple outcomes. Results We identified 13 studies for abstraction. Zinc supplementation decreased the proportion of diarrhoeal episodes which lasted beyond 7 days, risk of hospitalization, all-cause mortality and diarrhoea mortality. Using diarrhoea hospitalizations as the closest and most conservative possible proxy for diarrhoea mortality, zinc for the treatment of diarrhoea is estimated to decrease diarrhoea mortality by 23%. Conclusion Zinc is an effective therapy for diarrhoea and will decrease diarrhoea morbidity and mortality when introduced and scaled-up in low-income countries.